Measurement of Amorphous Peat Shear Strengthin the Direct Shear Box at High Displacement Rates - Amuda, Akeem Gbenga; Fauzan, Sahdi; Alsidqi, Hasan; Siti Noor Linda, Taib; Boylan, Noel; Aliaa, Mohamad (Springer Nature Switzerland, 2018)
The ASTM standard provides guidelines for the drained direct shear test (DST) and requires the samples to be sheared at rates estimated from time to failure, tf≥50t50 (where t50 is the time required to achieve 50% consolidation). This paper investigates the potential of estimating the undrained strength of peat in the DST owing to its ease of accessibility and simplicity over other laboratory tests. In this experimental study, peat samples were sheared at various displacement rates at tf/t50 values of 0.065–70. The samples tested at the ASTM specified rate of tf≥50t50 exhibit continuous increase and decrease in shear stress and volume respectively with increasing shear strain. Hence, determining the drained strength properties of peat in the DST apparatus is complicated. However, it is concluded that the shear stress ratio, τ/σ′v of the DST test samples sheared at rates corresponding to tf≤0.2t50, reasonably corresponds to that measured in undrained direct simple shear (DSS) tests on peat, found in the literature. Therefore, DST conducted at high displacement rates will be adequate for preliminary evaluation of the shear strength of peat at close to undrained conditions, when constant volume DSS apparatus is not available.